Efecto de la temperatura, humedad y dieta sobre el desarrollo de gnathocerus cornutus fab. (coleopera: tenebrionidae) (1989)
The influence of temperature, relative humidity' and diet composition in the duration and velocity of the deveJopmen t cicle of Gnathocerus comutus Fab. was studied. Each of two diets (Aand B) was tried in presence of 5 different  combinations of temperature and humidity. Optimal conditions for development were found to be: 28°C and 85-90% R.H.. in which the complete cycle lasts 54 days. the larval stage is the critical one in the development. in which a high variation among individuals in both. velocity and span of development. are notorious. The cycle duration is virtually the same for both diets, but in the diet A, a better adaptability, expressed as a proportion of descendents. was observed. Life tables and surviving curves were made.